2016
DOI: 10.1590/2446-4740.03616
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages adhesion rate on Ti-6Al-4V substrates: polishing and DLC coating effects

Abstract: Introduction: Various works have shown that diamond-like carbon (DLC) coatings are able to improve the cells adhesion on prosthesis material and also cause protection against the physical wear. On the other hand there are reports about the effect of substrate polishing, in evidence of that roughness can enhance cell adhesion. In order to compare and quantify the joint effects of both factors, i.e, polishing and DLC coating, a commonly prosthesis material, the Ti-6Al-4V alloy, was used as raw material for subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In this study, DLC showed a significant decrease in monocyte count with a decreased monocyte CD62L expression—a response like that of the ceramics. DLC has been shown to slightly increase monocyte adhesion, with DLC coated rather than uncoated Ti6Al4V favoring cell adhesion …”
Section: Discussionmentioning
confidence: 99%
“…In this study, DLC showed a significant decrease in monocyte count with a decreased monocyte CD62L expression—a response like that of the ceramics. DLC has been shown to slightly increase monocyte adhesion, with DLC coated rather than uncoated Ti6Al4V favoring cell adhesion …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, due to the bioinert properties of titanium, the bone formation rate (osseointegration) is very slow in the body 6 . Properties such as surface chemistry, texture, and wettability play a key role to accelerate the osseointegration of dental implants 7 . Hydrophilicity can alter bone cell adhesion, proliferation, and differentiation properties 8 .…”
Section: Introductionmentioning
confidence: 99%